Impact of entrepreneurial orientation and risk sharing on organizational performance influencing role of news media and public opinion - Zhang, Zhixiu; Xing, Yunwen (Frontiers in Psychology, 2023)
An entrepreneurial orientation is a method of implementing a strategy that makes use of a variety of resources that are owned by organizations. Entrepreneurial orientation is one of the primary factors that led to the company's founding. Risk sharing is a useful tactic that can be implemented by businesses in order to mitigate the amount of risk to which they are exposed. As a consequence of this, the objective of the research is to ascertain how the performance of an enterprise can be affected by the presence of both an entrepreneurial orientation and shared risk. The proliferation of news media has led to modifications in the ways in which businesses carry out their day-to-day operations, which in turn has an effect on the overall success of the organization. As a direct consequence of this, the research looked into the function that the news media play as a moderator of the connections that exist between entrepreneurial orientation, risk sharing, and the level of performance achieved by organizations. Even for enormous, well-known businesses that are active on a global scale, damaging publicity has the potential to lower the value of their companies. The aim of this stud was to investigate the impact of entrepreneurial orientation and risk sharing on organizational performance with the mediating role of news media and moderating role of public opinion. In order to achieve the objective of the study, a quantitative research approach was utilized. Data were collected from 450 managers of SMEs with the help of a questionnaire that was adapted from previous studies. A simple random sampling technique was used to collect data. The findings of the study showed that the relationship between entrepreneurial orientation, risk sharing, and organizational performance is positive and significant. The findings also showed that news media significantly mediated this relationship and public opinion moderated the relationship between news media and organizational performance. The current study has some practical and managerial implications which help SMEs to increase their performance.